The Klansman - Young, Terence, 1915-1994; Marvin, Lee; Burton, Richard, 1925-1984; Simpson, O. J., 1947-; Huie, William Bradford, 1910-1986.; Atlanta Productions; Cinetel Films ([Atlanta, GA] : The Atlanta Company, 1974)
When a young white woman is raped and a black man is accused, a small Alabama town ignites in racial tension. Caught in the middle of the conflict are the sheriff and a Southern aristocrat who attempt to keep the peace while protecting their traditional way of life. Features O.J. Simpson in his film debut.
Based on the novel by William Bradford Huie.
Lee Marvin, Richard Burton, Cameron Mitchell, Lola Falana, Luciana Paluzzi, O.J. Simpson.
Cinematographer, Lloyd Ahern; editor, Gene Milford; music, Dale D. Warren and Stu Gardner.
In English or Spanish; with optional Spanish subtitles.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 21, 2015)
Keywords: Ku Klux Klan (1915- ) -- Drama; Racism -- Alabama -- Drama; Race relations -- Drama; Film adaptations; Feature films; Internet videos; Streaming video